Bleeding Outcomes After Dental Extraction in Patients Under Direct-Acting Oral Anticoagulants vs. Vitamin K Antagonists: A Systematic Review and Meta-Analysis - Hua, Wenbing; Huang, Zhengmei; Huang, Zhuoli (Frontiers in Pharmacology, 2021)
Background: The current systematic review aimed to compare bleeding outcomes in dental extraction patients receiving uninterrupted Direct-acting oral anticoagulant (DOAC) or Vitamin K antagonists (VKAs) for various systemic diseases Methods: PubMed, Embase, ScienceDirect, CENTRAL and Google Scholar databases were searched for randomized controlled trials, controlled clinical trials, prospective and retrospective cohort studies, and case control studies, conducted on adult patients undergoing dental extraction under uninterrupted DOAC or VKAs therapy and reporting bleeding outcomes. The search was conducted up to 31st March 2021. We pooled data to calculate risk ratios (RR) with 95% confidence intervals (CI) in a random-effects model. Results: Eight studies comparing 539 patients on DOAC therapy and 574 patients on VKAs were included. Meta-analysis indicated a statistically significant lower bleeding risk in patients under DOAC therapy (RR 0.68 95% CI 0.49, 0.95 I2=0%). However, on sensitivity analysis, the results were statistically non-significant after exclusion of any of the included studies. On pooled analysis of limited number of studies, we found no statistically significant difference in the risk of bleeding between apixaban (RR 0.85 95% CI 0.45, 1.60 I2=0%), rivaroxaban (RR 0.95 95% CI 0.36, 2.48 I2=45%), dabigatran (RR 0.49 95% CI 0.19, 1.28 I2=5%), edoxaban (RR 0.41 95% CI 0.13, 1.27 I2=0%) and VKAs. Conclusion: The results of the first review comparing bleeding outcomes after dental extraction in patients on uninterrupted DOAC or VKA therapy indicates that patients on DOAC may have a reduced risk of hemorrhage. Current evidence is of very low-quality and should be interpreted with caution. Data on individual DOAC is scarce and at this point, the difference in the risk of bleeding between these drugs cannot be elucidated. Further studies with a large sample size shall supplement our conclusions.